Emerging research in artificial intelligence and computational intelligence international conference, AICI 2011, Taiyuan, China, September 23-25, 2011. proceedings - International conference on artificial intelligence and computational intelligence (2011 Taiyuan Shi, China); Deng, Hepu.; Miao, Duoqian; Wang, Fu Lee.; Lei, Jingsheng; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes, together with LNAI 7002, LNAI 7003, and LNAI 7004, the refereed proceedings of the International Conference on Artificial Intelligence and ComputationaI Intelligence, AICI 2011, held in Taiyuan, China, in September 2011. The 265 revised full papers presented in the four volumes were carefully reviewed and selected from 1073 submissions. The 83 papers presented in this volume are organized in topical sections on applications of artificial intelligence; applications of computational intelligence; automated problem solving; brain models/cognitive science; data mining and knowledge discovering; expert and decision support systems; fuzzy logic and soft computing; intelligent agents and systems; intelligent control; intelligent image processing; intelligent scheduling; intelligent signal processing; natural language processing; nature computation; neural computation; pattern recognition; rough set theory.
Electronic reproduction.
Keywords: Artificial intelligence -- Congresses; Computational intelligence -- Congresses; Electronic books